Late Mesolithic lifeways and deathways at Vlasac (Serbia). (February 2014) - Borić, Dušan; French, Charles A. I.; Stefanović, Sofija; Dimitrijević, Vesna; Cristiani, Emanuela; Gurova, Maria; Antonović, Dragana; Allué, Ethel; Filipović, Dragana
<x content-type="archive" xml:space="preserve">Abstract</x> Recent excavations (2006–2009) at the Mesolithic-Neolithic site of Vlasac in the Danube Gorges region of the north-central Balkans have focused on a reevaluation of previous conclusions about site formation processes, stratigraphy, chronology, and the nature of occupation. Mostly Late Mesolithic remains had been encountered in the preserved portion of the site, but, for the first time, in a restricted zone of the excavated area, vertical stratification of burial and occupation features yielded evidence about the use of the site in the period that is contemporaneous with Phase I–II at Lepenski Vir, the Mesolithic-Neolithic transition phase in this region, ca. 6200–5900 calb.c. Various strands of archaeological evidence show both continuities and discontinuities in Late Mesolithic forager life- and deathways at the start of the Neolithic in the central Balkans.